2019
DOI: 10.1021/acs.jpcc.9b08710
|View full text |Cite
|
Sign up to set email alerts
|

Systematical Investigation of Chain Length Effect on the Melting Point of a Series of Bifunctional Anthraquinone Derivatives via X-ray Diffraction and Scanning Tunneling Microscopy

Abstract: Introducing a continuously changing alkyl chain is effective to modify the conjugated molecule, which is widely used in studying the diversity of two-dimensional (2D) self-assembly and the performance of three-dimensional (3D) bulk materials. In this study, a series of bifunctional anthraquinone derivatives (A-OC n , n = 3−18) are synthesized to investigate the interrelation between the chain length and the melting point by differential scanning calorimetry (DSC). It is observed that the A-OC n (n = 1 and 4) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…This odd–even effect in melting point is ascribed to the different packing modes of alkanes in the solid state . A similar alternative melting point is also observed in alkyl chain-engineered functional materials . Besides the melting point, the odd–even effects in other material properties such as solubility, nanoparticle morphology, endothermic enthalpy, phosphorescence lifetime, and crystal structures are also reported.…”
Section: Introductionsupporting
confidence: 57%
“…This odd–even effect in melting point is ascribed to the different packing modes of alkanes in the solid state . A similar alternative melting point is also observed in alkyl chain-engineered functional materials . Besides the melting point, the odd–even effects in other material properties such as solubility, nanoparticle morphology, endothermic enthalpy, phosphorescence lifetime, and crystal structures are also reported.…”
Section: Introductionsupporting
confidence: 57%
“…However, the X-ray and the STM data are separated in such a manner that the former are presented for shorter substituents (from butoxy to hexyloxy), whereas the latter are limited to longer substituents (from heptyloxy to octadecyloxy). The present paper is complementary to ref , since in addition to detailed electrochemical results it provides complete STM and X-ray data for Anth derivatives with substituents varying in the range from butoxy to dodecyloxy. This set of results not only allows for establishing the relationship between the 3D organization in single crystals and the 2D one in monolayers but also demonstrates that along with the increasing length of the substituent the effect of the graphite substrate symmetry on the resulting 2D supramolecular organization becomes more pronounced.…”
Section: Introductionmentioning
confidence: 72%
“…Several papers on Anth-containing alkoxy groups have been published to date, including those reporting STM investigations on monosubstituted, 34 disubstituted, 35 and trisubstituted 36 derivatives. In particular, a very recently published, extremely interesting paper 37 describes 3D and 2D structural properties of dialkoxy-substituted Anth. However, the X-ray and the STM data are separated in such a manner that the former are presented for shorter substituents (from butoxy to hexyloxy), whereas the latter are limited to longer substituents (from heptyloxy to octadecyloxy).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length. 29,30 In contrast, OC12-salpn, a salen derivative with a methyl group introduced as steric bulk, exhibited cold crystallization.…”
Section: Introductionmentioning
confidence: 99%